(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study investigated the availability of infrastructural facilities for the establishment of entrepreneurship centres in universities in South East Nigeria. One research question guided the study with two hypotheses tested at 0.05 level of significance. Descriptive survey research design was adopted. The population was 116 employees from eight Entrepreneurship Centres in South East Nigeria. A researcher-developed questionnaire comprising 11 items and validated by experts in the field was used to collect data. A pilot test was conducted with the instrument and the application of the Cronbach Alpha on the data collected yielded coefficient value of 0.76. Mean ratings and standard deviation were used to analyze data in respect of the research questions while z-test was used to test the null hypotheses. The findings revealed that infrastructural facilities needed for the smooth operation of Entrepreneurship Centres in universities were available in line with the NUC guideline. It was recommended among others, that Government and other stakeholders in education should continue to provide infrastructural facilities and equipment in all entrepreneurship centres. It was also recommended that a review of the state of infrastructure and equipment in the centres should be carried out on a regular basis so as to avoid dilapidation and spoilage.